2017
DOI: 10.3390/ijms18122510
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Protocatechuic Acid Reduces Traumatic Brain Injury-Induced Neuronal Death

Abstract: Protocatechuic acid (PCA) was first purified from green tea and has shown numerous biological activities, including anti-apoptotic, anti-inflammatory, and anti-atherosclerotic effects. The effect of PCA on traumatic brain injury (TBI)-induced neuronal death has not previously been evaluated. TBI is defined as damage to the brain resulting from external mechanical force, such as rapid acceleration or deceleration, impact, blast waves, or penetration by a projectile. TBI causes neuronal death in the hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Neuronal apoptosis occurs through multiple cellular mechanisms, following secondary neuronal injury, after a primary brain injury [61]. It was found that RAGE activation induces inflammation, oxidative stress, and apoptosis via upregulation of NF-κB [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal apoptosis occurs through multiple cellular mechanisms, following secondary neuronal injury, after a primary brain injury [61]. It was found that RAGE activation induces inflammation, oxidative stress, and apoptosis via upregulation of NF-κB [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…46 Similar enhancement of microglial/astrocytes population after traumatic injury has been shown in several studies. [54][55][56]61 Gradual decrease in the number of degenerating neurons in injured and treated with IFN-γ (I + IFN-γ) and IL-1β (I + IL-1β) groups from first day to seventh day postinjury may be due to specific trophic neuroprotective effects of IFN-γ and IL-1β directly or through enhancement of microglia and astrocytes, thereby enhancing the neurotrophic factors such as BDNF as observed in this study, which may be one of the many neurotrophic factors provided neuroprotection. We have reported similar enhancement of astrocytes, microglia and BDNF by dibutyryl cyclic adenosine monophosphate (dBcAMP), a synthetic analogue of cAMP.…”
Section: Il-1β Are Able To Increase Secretion Of Bdnf Through Astrocymentioning
confidence: 99%
“…In the present study, we used PCA (30 mg/kg, i.p.) [ 21 ] on a pilocarpine-induced animal seizure model. Here, we found that treatment with PCA after a seizure decreased oxidative injury, microglia activation, and neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%